Study Articles In The Journal Of Studies In Arabic Language And Literature From A Content Analysis Perspective/ Ø¯Ø±Ø§Ø³Ø© Ù…Ù‚Ø§Ù„Ø§Øª Ù…Ø¬Ù„Ø© Ø¯Ø±Ø§Ø³Ø§Øª ÙÙŠ Ø§Ù„Ù„ØºØ© Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© ÙˆØ¢Ø¯Ø§Ø¨Ù‡Ø§ Ù…Ù† Ù…Ù†Ø¸Ø§Ø± Ø§Ù„ØªØÙ„ÛŒÙ„ Ø§Ù„Ù…ØØªÙˆÛŒ ÙˆØ§Ù„Ø§Ù‚ØªØ¨Ø§Ø³ÙŠ - Bavanpouri, Masoud; Gheibi, Abdulahad; Kazem Alilu, Sohaila (Ijaz Arabi Journal of Arabic Learning, 2021)
As articles' production is growing at an increasing rate in Iran and the world, there is an urgent need for criteria to evaluate scientific publications. This will be achieved by using scientific evaluation. Who benefits from analyzing the information. The Journal of Studies in Arabic Language and Literature is considered one of the accredited and essential magazines in Arabic language and literature in Iran. University and educational institution. This article dealt with a statistical and analytical study of the number of article writers, their testimonies, the extent of cooperation between them, the centers and institutions active in the magazine. Moreover, From this standpoint, the article obtained the following results: 85 articles were written individually, 101 articles were also written jointly, 77 articles were jointly written with the cooperation of university colleagues, and 24 articles were written with the cooperation of different persons from different universities. Shaker Al Ameri and Wafiq Mahmoud Solitain became the most prolific authors with eight articles. Half of the essay topics are devoted to criticism, fiction, and text analysis. Fifty articles were written by the editorial staff with an average of 88/26, which is a large number.